SEMANTIC ROLES ON TOURISM NARRATIVE TEXTS FOUND IN WEB - Tri Sukarsih, Ni Nyoman; Lindawati, Ni Putu; Lee, Cakra Sagiarta; Mambrasar, Gina Ivana; Putra Tanaya, Aditya Permana (Akademi Komunitas MAPINDO, 2022)
This study aimed to determine the types of semantic roles and its phenomenon related to the utilizations of types of semantic roles on 3 chosen hotel websites. The phenomenon related was the language of hospitality namely English for Tourism Purposes (ETP) which is a necessity in hospitality field. The study conducted the qualitative method for content analysis to analyse 10 web pages of each three hotels through observation and comprehensive structural analysis (Roller, 2019: 2). The end result of the study were its correlation with the ETP and concluded in a statistics and showed based on the three hotels combined as follows: agent (465) times, patient (1,101) times, theme (564) times, experiencer (16) times, beneficiary (221) times, instrument (289) times, location (397) times, goal (93) times, source (116) times, and stimulus (89) times. Keywords: Kempinski Hotel, Sixsenses Hotel, Discovery Kartika Plaza Hotel, Semantic Roles, Web Pages.